2011
DOI: 10.5296/jbls.v3i1.1499
|View full text |Cite
|
Sign up to set email alerts
|

General Assumption of Psychological Behavior Based on Finger Print Pattern

Abstract: The impressions from the pulp of finger are known as fingerprints. Using fingerprints to identify indi­viduals has become an invaluable tool worldwide. A Study of finger print pattern was performed in the prisoners and normal population (non prisoners) of hilly region to compare whorls, loops, arches and composites in each hand using ink technique. The goal of the study was to identify the behavioral traits (somatic, psychological and Neurological) of these two groups on the basis of finger print pattern. Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Whorl and loop patterns were relatively higher on the left and right digit of the control compared with the criminals, and this was in line with the study conducted by Agarwal 15 .…”
Section: Discussionsupporting
confidence: 90%
“…Whorl and loop patterns were relatively higher on the left and right digit of the control compared with the criminals, and this was in line with the study conducted by Agarwal 15 .…”
Section: Discussionsupporting
confidence: 90%
“…Agarwal et al observed that individuals with loops were found to have a possible lack of concentration while individuals with whorls are quite aggressive. 25 White mentioned that whorl pattern was associated with individuals who were very selective and otherwise non-committal. 26 Singh and Majumdar found that individuals with whorls are quite aggressive and obstinate, whereas, people with arches on any finger are settled, skillful, and socializing.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that individual behavior and personality differ according to fingerprint type (Singh and Majumdar 2015;Shrestha et al 2016). Generally, fingerprint patterns are categorized as loop, whorl, or arch patterns, accounting for 60-65%, 30-35%, and 5% of all fingerprints, respectively (Agarwal et al 2012). Singh et al 2016 suggested that individuals with arch-type fingerprints prefer a simple lifestyle and like to communicate with others.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a poor resolution of an image, the procedure was repeated. Recognition and classification of the fingerprints were performed based on standard classifications by a trained dentist separately and blindly (Henry 1937;Agarwal et al 2012). The trained and calibrated dentist classified the fingerprint patterns twice for each subject.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation